Teachers Resource Guide for Western Literature Themes and Writers - Carlsen, G. Robert (St. Louis McGraw-Hill, Inc, 1967)
This book contains five vital themse: Conflict of Wills, Know Thyself, The Foibles of Man, Choice and Consequence, and Critics of Society. The editors have carefully structured each theme to promote the progressive understanding of its meaning. After the reader has encountered the theme in the major work, he then traces the theme through the shorter selections which make up the remainder of each unit.
Keywords: Literature